Efficacy of oral metformin in a patient with metastatic adrenocortical carcinoma: Examination of mechanisms and therapeutic implications. (30th January 2018) - Peixoto, RD; Gomes, LM; Sousa, TT; Racy, DJ; Shigenaga, M; Nagourney, RA
Although rare, adrenocortical carcinoma is among the most common tumors found in children with Li-Fraumeni syndrome and Li-Fraumeni-like syndrome, associated with germ-line mutations in the TP53 gene. In southern Brazil, one form of Li-Fraumeni syndrome, associated with childhood adrenocortical carcinoma, is caused by a mutation in the R337H TP53 tetramerisation domain and is attributed to a familial founder effect. Adrenocortical carcinoma is considered an aggressive neoplasm, usually of poor prognosis and is generally unresponsive to systemic chemotherapy. Optimal treatment regimens remain to be established. We report the case of a young woman with metastatic adrenocortical carcinoma, who achieved stable disease with mitotane, cisplatin, doxorubicin, and etoposide as first-line therapy, but then had an objective response to oral metformin that lasted 9 months. The presence of the R337H TP53 mutation suggests a mechanism for the observed response to metformin.